2012
DOI: 10.1002/cctc.201200469
|View full text |Cite
|
Sign up to set email alerts
|

Pt/Al2O3 Catalyzed 1,3‐Propanediol Formation from Glycerol using Tungsten Additives

Abstract: Screening of four commercial catalysts (Pt/Al2O3, Pt/SiO2, Pd/Al2O3, and Pd/SiO2) and four acidic additives (hydrochloric, tungstic, phosphotungstic, and silicotungstic acids) shows that the combination of a platinum hydrogenation catalyst with tungsten containing acidic additives yields 1,3‐propanediol from aqueous glycerol. The performance of the best catalytic system Pt/Al2O3 with silicotungstic acid as an additive was optimized by experimental design, capturing the influence of reaction time, glycerol conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(31 citation statements)
references
References 27 publications
2
22
0
7
Order By: Relevance
“…Hanefeld and co-workers studied the effect of tungstic acid during Pt/Al 2 O 3 catalyzed the hydrogenolysis of glycerol. [51] It showed that the selectivity for 1,3-PDO was significantly improved by adding the H 2 WO 4 additive. It was possible that a glycerol tungstic acid ester was formed as an intermediate, which led to the selective formation of 1,3-PDO.…”
Section: Entrymentioning
confidence: 99%
See 3 more Smart Citations
“…Hanefeld and co-workers studied the effect of tungstic acid during Pt/Al 2 O 3 catalyzed the hydrogenolysis of glycerol. [51] It showed that the selectivity for 1,3-PDO was significantly improved by adding the H 2 WO 4 additive. It was possible that a glycerol tungstic acid ester was formed as an intermediate, which led to the selective formation of 1,3-PDO.…”
Section: Entrymentioning
confidence: 99%
“…Hanefeld and co‐workers studied the effect of tungstic acid during Pt/Al 2 O 3 catalyzed the hydrogenolysis of glycerol [51] . It showed that the selectivity for 1,3‐PDO was significantly improved by adding the H 2 WO 4 additive.…”
Section: Tungsten‐containing Bifunctional Catalysts For the Selectivementioning
confidence: 99%
See 2 more Smart Citations
“…reported that tungstic acid improved 1,3‐PDO selectivity on Rh‐based catalysts. ten Dam et al . screened four commercial catalysts and four acidic additives for glycerol hydrogenolysis and achieved 28 % 1,3‐PDO selectivity with 49 % conversion on Pt/Al 2 O 3 with silicotungstic acid as an additive.…”
Section: Introductionmentioning
confidence: 99%